Investigação da atividade de extratos orgânicos de Piper dicaricatum e suas frações sobre a germinação e crescimento do alface - Martins, Silvânia Alves (2017)
Allelopathy is the phenomenon by which a vegetal specie influences in growth of 35 another around it. Several species have already been identified with this ability, but few 36 studies have been reported with genus Piper. The present work aimed to evaluate the 37 bioactivity of P. divaricatum by using organic extracts and their fractions, in order to 38 identify allelochemicals responsible for growth inhibition of plants, based on lettuce, as 39 reference. Seeds were put to germinate in Petri dishes containing filter paper soaked in 1 40 ml of each organic extract and their respective fractions. Plates were incubated in BOD 41 for 7 days. Identification of the allelochemicals was done by thin layer chromatography. 42 It was verified that the chloroform fraction of the aqueous extract showed high 43 inhibition to germination and growth of lettuce seedlings. Alkaloids and coumarins were 44 identified in this fraction, both reported in the literature as potent inhibitors of 45 germination because cause alterations in cell division processes besides tissue damages 46 and interference in transport of membrane solutes. Other allelochemicals were also 47 identified in fractions of ethanol/methanol extract, such as terpenes/triperpenes, fatty 48 acids, flavonoids and phenylpropanoids, all involved in plant defense response. Two 29 49 other compounds, fatty acids and anthracene derivatives, have not yet been reported as 50 allelochemicals in Piper.